Clinical features and management issues of NAFLD-related HCC: what we know so far. (2nd January 2023) - Pugliese, Nicola; Alfarone, Ludovico; Arcari, Ivan; Giugliano, Silvia; Parigi, Tommaso Lorenzo; Rescigno, Maria; Lleo, Ana; Aghemo, Alessio
ABSTRACT: Introduction: Nonalcoholic fatty liver disease (NAFLD) is replacing viral hepatitis as the leading cause of chronic liver disease and hepatocellular carcinoma (HCC) in many Western countries. NAFLD-associated HCC usually affects older patients with multiple comorbidities, frequently develops in the absence of cirrhosis, and is often diagnosed later with worse chance of survival. The worse prognosis is also due to limited surveillance strategies and a lower efficacy of standard treatments. Areas covered: We evaluate the available literature to understand the current surveillance strategies and treatment limitations in the workup of NAFLD-associated HCC, focusing on the differences with HCC associated with other liver diseases. Expert opinion: In this review we discuss epidemiology and risk factors for HCC in NAFLD patients and address key HCC surveillance and management issues. Although most data are still preliminary, the detection of non-cirrhotic NAFLD patients at increased risk for HCC and the potential adoption of novel screening tools could lead to accurate and suitable HCC surveillance and management strategies for NAFLD patients.